Crystallization and preliminary X‐ray crystallographic analysis of UDP‐glucuronic acid:flavonol‐3‐O‐glucuronosyltransferase (VvGT5) from the grapevine Vitis vinifera. Issue 1 (8th January 2013) - Mizohata, Eiichi; Okuda, Takuma; Hatanaka, Seika; Nakayama, Taisuke; Horikawa, Manabu; Nakayama, Toru; Ono, Eiichiro; Inoue, Tsuyoshi
<x xml:space="preserve">Abstract</x> Grapevine (Vitis vinifera) glycosyltransferase 5 (VvGT5) is a UDP‐glucuronic acid:flavonol‐3‐O‐glucuronosyltransferase that catalyses the 3‐O‐specific glucuronosylation of flavonols using UDP‐glucuronic acid as a sugar donor to produce flavonol 3‐O‐glucosides, which are important bioactive phytochemicals. Recombinant VvGT5 expressed in Escherichia coli cells was purified and crystallized by the sitting‐drop vapour‐diffusion method. A full set of X‐ray diffraction data was collected to 2.2 Å Bragg spacing from a single crystal using a synchrotron‐radiation source. The crystal was hexagonal, belonging to space group P6122, with unit‐cell parameters a = b = 102.70, c = 535.92 Å. The initial phases were determined by the molecular‐replacement method.